PCR-RFLP analysis of non-coding regions of cpDNA in Araucaria angustifolia (Bert.) O. Kuntze - Schlögl,Paulo Sérgio (2007)
The Araucaria angustifolia (Bert.) O. Kuntze, also named the "paraná pine" (pinheiro-do-Paraná in Portuguese), is a native conifer species naturally occurring in the Brazilian Tropical Atlantic Forest which in Brazil is mostly limited to the southern Brazilian states of Paraná, Santa Catarina and Rio Grande do Sul. Chloroplast DNA markers (cpDNA) are useful in populational genetic studies because of their low substitution rate and the uniparental transmission. The conservation of cpDNA genes between species has allowed the design of consensus chloroplast primers that have had a great impact on population genetics and phylogenetic studies. In this study we used the polymerase chain reaction technique combined with restriction enzyme fragment length polymorphism (PCR-RFLP) to characterize the genetic diversity of the chloroplast genome in nine natural A. angustifolia populations. Among the 141 trees surveyed we found 12 different cpDNA haplotypes and demonstrated that A. angustifolia has high levels of total diversity (hT = 0.612) and an average within-population diversity (hS) of 0.441, suggesting the presence of high within-population variation. The estimated genetic divergence could be helpful in designing breeding programs and species conservation strategies, although additional studies with a larger number of populations and trees is essential for a better understanding of gene flow and the inheritance of major Araucaria angustifolia traits.